The Acute Physiology and Chronic Health Evaluation II score is helpful in predicting the need of relaparotomies in patients with secondary peritonitis of colorectal origin (Swiss Medical Weekly, 2012)
BACKGROUND: Secondary peritonitis of colorectal origin has considerable morbidity and mortality. Relaparotomies are frequently neccessary in the course of the disease. The objective of this study was to evaluate several scores in terms of their predictive value, i.e. whether Mannheim Peritonitis Index (MPI), Acute Physiology And Chronic Health Evaluation (APACHE) II, or Colorectal Physiological and Operative Severity Score for the Enumeration of Mortality and Morbidity (CR-POSSUM) scores can predict relaparotomies. METHODS: Charts of 147 patients treated for secondary peritonitis of colorectal origin were retrospectively reviewed, MPI, APACHE II, and CR-POSSUM scores were calculated, and groups of patients with or without relaparotomies were compared. RESULTS: Thirty-four percent of patients underwent one or more relaparotomies. Patients with relaparotomies showed a significantly higher APACHE II score than patients without relaparotomies (p = 0.004). MPI (p = 0.072) and CR-POSSUM score (p = 0.319) did not differ between the two groups. A high APACHE II score was also significantly associated with the need for a relaparotomy on demand (p